H19 regulates trophoblastic spheroid adhesion by competitively binding to let-7. Issue 5 (May 2019) - He, Dongmei; Zeng, Hong; Chen, Jingfei; Xiao, Lan; Zhao, Yuhao; Liu, Nenghui
Abstract : Integrin β3 ( ITGB3 ), which is the target gene of the miRNA let-7 that can be antagonized by long noncoding RNA (lncRNA) H19, is well known to have a critical role in endometrium receptivity. However, the regulation of ITGB3 in cell–cell or cell–extracellular matrix adhesion and invasion for the maintenance of early pregnancy remains unknown. This study aimed to explore the role of the H19/let-7/ITGB3 axis in regulating trophoblastic spheroid adhesion and in vitro invasion ability using the HTR-8/SVneo cell line and to investigate the expression levels of lncRNA H19 and ITGB3 in human products of conception. The in vitro knockdown of H19 resulted in decreased expression of ITGB3 at the mRNA and protein levels and reduced the adhesion and invasion ability. In the embryonic chorion tissue of spontaneous abortion (SA), the expressions of H19 and ITGB3 at both the mRNA and protein levels decreased. The results of quantitative RT-PCR, Western blot analysis, dual-luciferase report gene and functional miRNA let-7 rescue experiments, adhesion assay and in vitro transwell invasion assay confirmed that H19 regulated trophoblastic spheroid adhesion with endometrial stromal cells through the H19/let-7/ITGB3 axis, thereby providing an improved understanding of the molecular mechanism of SA.